Impact of fish pond sediments amendment and sawdust mulch on the performance of sesame (Sesamum indicum L.) in a southern Guinea savanna zone of Nigeria: IMPACT OF FISH POND SEDIMENTS AND SAWDUST MULCH ON THE PERFORMANCE OF SESAME - E K EIFEDIYI,; O M YAHYA,; F O OGEDEGBE,; A A OLAYODE,; S O OGUNTOYE,; Y J ABDULKAREEM, (Journal of Oilseeds Research, 2026)
The increasing demand for fish as a source of animal protein has led to the widespread establishment of fish ponds across Nigerian communities. However, this development has introduced the challenge of disposing pond sediments, which, if not properly managed, may lead to environmental pollution. Despite this, pond sediments are rich in organic matter and can serve as effective soil amendments. To explore this potential, a field experiment was conducted at the Teaching and Research Farm of the University of Ilorin during the 2020 and 2021 cropping seasons. The study assessed the impact of fishpond sediments and sawdust mulch on the growth and yield of sesame. Treatments imposed were pond sediments at 0, 7.5, and 15 mg/ha, and sawdust mulch at 0, 5, 10, and 15 mg/ha. The experiment was a factorial arrangement in a randomized complete block design (RCBD) with four replications. Data were collected on various growth and yield parameters, such as plant height, number of leaves, and number of capsules, length of capsules, yield, crude protein and lipid contents. Results indicated that applying pond sediments at 15 mg/ha enhanced plant height, leaf area, number of leaves, yield, and crude protein content. The combined use of sawdust mulch and fishpond sediment proved effective as an organic amendment for sesame cultivation in this region.